Metrological characterization of an hexapod-shaped Multicomponent Force Transducer. (January 2016) - Genta, Gianfranco; Germak, Alessandro; Barbato, Giulio; Levi, Raffaello
Abstract: A Multicomponent Force Transducer (MFT) was devised by INRiM for a specific request in railway industry, entailing measurement of two force components (transversal and axial force). Measurement of other components, while not strictly required, was deemed helpful for practical use. INRiM, basing on its experience, developed and calibrated a full six-component hexapod-design prototype of MFT. Best Subset Regression was applied to identify parsimonious models linking applied components to MFT outputs. Finally, the uncertainty associated to the values of transversal and axial force was evaluated.